Domestication and Foreignization in Translating American Prose for Slovenian Children - Mazi-Leskovar, Darja (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThe purpose of this article is to describe and explore the examples of domestication and foreignization in translations of American prose read by Slovenian children. A few of the earlier American books that have entered the children’s literature canon have been read by dual audience and among these Uncle Tom’s Cabin has the longest tradition. The translations of the novel are presented in the light of domestication and foreignization endeavours. In order to complete and expand the picture of translating for children, a few additional works published in different eras of Slovenian translation history are briefly discussed.